Komunikasi Kekerabatan Mahasiswa Batak dalam Interaksi Sosial Digital di Lingkungan Universitas Medan Area - Oktaviani, Nurliza; Suharyanto, Agung (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2025)
Kinship communication is a vital aspect of Batak culture, reflecting social structure, identity, and group norms. Within the multicultural setting of Universitas Medan Area, Batak students continue to carry these values into their daily interactions, including those conducted digitally. This study aims to examine the forms and dynamics of Batak students’ kinship communication, both in face-to-face and online interactions, through the lenses of symbolic interactionism and social identity theory. A qualitative method with a phenomenological approach was employed, involving eight purposively selected informants from various faculties. Data collection techniques included semi-structured interviews and limited observation of digital interactions. The findings reveal that Batak students consistently use kinship address terms such as tulang, amang, and namboru as symbols of respect for clan hierarchy, serving both as social control and expressions of collective identity. Moreover, digital media does not diminish these values but instead acts as a medium for cultural preservation and expansion. Students form online communities based on clan affiliation, maintain verbal etiquette, and strengthen solidarity through coordinated support and emotional connection. In conclusion, Batak students’ kinship communication proves to be adaptive, thriving not only in physical spaces but also contextually within digital environments. Traditional values remain relevant and are actively maintained, bridging culture and technology in a harmonious way.